The effects of treadmill exercise and diet control on cognitive function in HFD-induced ApoE-/- mice based on the SIRT1-NF-κB/PGC-1α-BDNF signaling pathways - Xu Ting; Deng Wenjuan; Li Shufeng; Liu Yi; Shi Zhitong; Zhang Xiaoyue; Wang Ningping (Guoji laonian yixue zazhi)
[Objective] To investigate the effect and mechanism of treadmill exercise and diet control on cognitive dysfunction in apolipoprotein E knockout(ApoE-/-)mice model. [Methods] Forty ApoE -/- male mice fed a high-fat diet for 8 weeks were randomly and equally divided into a high-fat diet exercise (HFD + TR) group, a high-fat diet rest (HFD + SED) group, a diet-controlled exercise (DC + TR) group, and a diet-controlled rest (DC + SED) group, with 10 mice in each group. HFD + TR group and HFD + SED group continued to be fed with high-fat diet for 10 weeks, DC + TR group and DC + SED group switched to standard diet for 10 weeks, and the food intake was controlled to 70% of the normal intake, while treadmill exercise intervention was performed in HFD + TR group and DC + TR group. Morris water maze test was used to evaluate the cognitive function of mice, enzyme-linked immunosorbent assay (ELISA) was used to detect the serum levels of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), and real-time PCR (RT-qPCR) was used to detect the expression levels of silent information regulator 1 (SIRT1), nuclear transcription factor NF-κB (NF-κB), peroxisome proliferation receptor gamma coactivator α (PGC-1α), and brain-derived neurotrophic factor (BDNF) in the hippocampus. [Results] The results of water maze test showed that diet control and treadmill exercise could improve spatial learning and memory ability of mice. The results of ELISA and RT-qPCR showed that diet control and treadmill exercise could decrease the levels of inflammatory cytokines TNF-α and IL-1β in the serum of mice, and also decrease the expression levels of NF-κB mRNA in the hippocampus of mice, but increase the expression levels of SIRT1, PGC-1α, and BDNF mRNA in the hippocampus of mice. [Conclusion] Treadmill exercise and diet control can reduce the inflammatory response in the hippocampus of mice by mediating the SIRT1-NF-κB/PGC-1α-BDNF signaling pathway, thereby improving cognitive function in mice.